2005
DOI: 10.1177/0032885504274289
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Mandated and Nonmandated New York City Jail Diversion for Offenders with Alcohol, Drug, and Mental Disorders

Abstract: The authors studied 175 mentally ill, substance-using adult jail detainees assessed at baseline, 3, and 12 months through a quasi-experimental comparison design. The study examines the effect of diversion, treatment, and individual characteristics on criminal justice, mental health, substance use, and life satisfaction outcomes. The intervention group included nonmandated and mandated diversion tracks. The comparison participants met diversion acceptance criteria but underwent standard criminal justice process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 54 publications
4
52
0
Order By: Relevance
“…Offenders with Downloaded by [Queensland University of Technology] at 16:20 01 November 2014 mental disorders who are detained and awaiting competency examination had 40 times the rate of homelessness compared to the general population and 21 times the rate homelessness compared with the non-criminal justice involved mentally ill New York City population (Martell, Rosner, & Harmon, 1995). Similar high rates of homelessness (63% in 12 months prior to arrest; 30% at arrest) were found for those competent and detained in New York City jails with diagnoses of co-occurring serious mental illness and addictive disorders (Broner, Mayrl, & Landsberg, 2005).…”
Section: Introductionsupporting
confidence: 55%
“…Offenders with Downloaded by [Queensland University of Technology] at 16:20 01 November 2014 mental disorders who are detained and awaiting competency examination had 40 times the rate of homelessness compared to the general population and 21 times the rate homelessness compared with the non-criminal justice involved mentally ill New York City population (Martell, Rosner, & Harmon, 1995). Similar high rates of homelessness (63% in 12 months prior to arrest; 30% at arrest) were found for those competent and detained in New York City jails with diagnoses of co-occurring serious mental illness and addictive disorders (Broner, Mayrl, & Landsberg, 2005).…”
Section: Introductionsupporting
confidence: 55%
“…The study by Lamberti and colleagues (2001) of a post-booking diversion program in Rochester, NY, documented a reduction in mean jail days, average arrests, and mean hospital days using a 12-month pre-post comparison. A study of New York City's LINK diversion program, comparing mandated and non-mandated divertees with nondiverted individuals, found that individuals in the mandated diversion track had fewer jail days, more time in the community, reduced substance use, and spent more time in treatment than non-mandated diverted or non-diverted individuals (Broner, Maryl, & Landsberg, 2005). Broner and colleagues (2005) concluded that structured programming and supervision increased the likelihood that diverted individuals would achieve positive outcomes.…”
mentioning
confidence: 99%
“…The findings indicate that diversion programs are associated with less days spent in jail (Steadman et al 1999;Hoff et al 1999;Christy et al 2005;Broner et al 2005;Lattimore et al 2003), longer time to re-arrest (McNiel and Binder 2007) and either reduced recidivism (Moore and Hiday 2006;Teller et al 2004;Trupin and Richards 2003) or produced no increase in recidivism rates when compared to people with serious mental illness processed in the traditional court system (Shafer et al 2004;Steadman et al 1999;Christy et al 2005). With regard to clinical outcomes, there is evidence that diversion programs are associated with reduced homelessness and psychiatric hospitalizations, and improvements in psychosocial functioning (Cosden et al 2005;O'Keefe 2006).…”
Section: Introductionmentioning
confidence: 97%